Identification of follistatin-like 1 by expression cloning as an activator of the growth differentiation factor 15 fene and a prognostic biomarker in acute coronary syndrome - Widera, Christian; Giannitsis, Evangelos; Katus, Hugo (Clinical chemistry, 2012)
BACKGROUND: Growth differentiation factor 15 (GDF15) is a stress-responsive cytokine and biomarker that is produced after myocardial infarction and that is related to prognosis in acute coronary syndrome (ACS). We hypothesized that secreted proteins that activate GDF15 production may represent new ACS biomarkers. METHODS: We expressed clones from an infarcted mouse heart cDNA library in COS1 cells and assayed for activation of a luciferase reporter gene controlled by a 642-bp fragment of the mouse growth differentiation factor 15 (GDF15) gene promoter. We measured the circulating concentrations of follistatin-like 1 (FSTL1) and GDF15 in 1369 patients with ACS. RESULTS: One cDNA clone that activated the GDF15 promoter-luciferase reporter encoded the secreted protein FSTL1. Treatment with FSTL1 activated GDF15 production in cultured cardiomyocytes. Transgenic production of FSTL1 stimulated GDF15 production in the murine heart, whereas cardiomyocyte-selective deletion of FSTL1 decreased production of GDF15 in cardiomyocytes, indicating that FSTL1 is sufficient and required for GDF15 production. In ACS, FSTL1 emerged as the strongest independent correlate of GDF15 (partial R2 = 0.26). A total of 106 patients died of a cardiovascular cause during a median follow-up of 252 days. Patients with an FSTL1 concentration in the top quartile had a 3.7-fold higher risk of cardiovascular death compared with patients in the first 3 quartiles (P < 0.001). FSTL1 remained associated with cardiovascular death after adjustment for clinical, angiographic, and biochemical variables. CONCLUSIONS: Our study is the first to use expression cloning for biomarker discovery upstream of a gene of interest and to identify FSTL1 as an independent prognostic biomarker in ACS.